MicroRNA‐31‐5p enhances the Warburg effect via targeting FIH. Issue 1 (13th July 2018) - Zhu, Biying; Cao, Xiuye; Zhang, Wenqiang; Pan, Guoping; Yi, Qing; Zhong, Wenbin; Yan, Daoguang
ABSTRACT: The enhanced expression of miR‐31 has been observed in many human malignancies including lung cancer, and this microRNA regulates several aspects of oncogenesis. However, the role of miR‐31‐5p in energy metabolism remains elusive. Here, we confirm that H1299 and A549 cells, 2 lung cancer cell lines, relay on aerobic glycolysis as main source of ATP. Inhibition of miR‐31‐5p leads to decreased glycolysis and ATP production, while miR‐31‐5p overexpression increases them. Hypoxia inducible factor 1 (HIF‐1) up‐regulates the expression of glycolytic enzymes, and the HIF‐1α inhibitor (FIH) inhibits HIF‐1 activity. Because FIH is a direct target of miR‐31‐5p, inhibition of miR‐31‐5p results in enhanced FIH expression and suppression of HIF‐1 signaling, while over‐expression of miR‐31‐5p has the opposite effects. Via this mechanism, miR‐31‐5p up‐regulates aerobic glycolytic genes and maintains energy homeostasis. To further validate the mechanism of miR‐31‐5p in glycolysis regulation, we show that overexpression or knockdown of FIH rescued the effects of miR‐31‐5p or miR‐31‐5p inhibitor on HIF activation and its target gene expression, respectively. Finally, by means of an A549 cell xenograft mouse model, we demonstrate that the miR‐31‐5p promotes cell proliferation via enhancing glycolysis. In summary, this study reveals that miR‐31‐5p promotes the Warburg effect via direct targeting of FIH.—Zhu, B., Cao, X., Zhang, W., Pan, G., Yi, Q., Zhong, W., Yan, D. MicroRNA‐31‐5p enhances the Warburg effect via targeting FIH. FASEB J. 33, 545–556 (2019). www.fasebj.org